Centrosome replication, genomic instability and cancer - Krämer, Alwin; Neben, Kai; Ho, Anthony Dick (Leukemia, 2002)
Karyotypic alterations, including whole chromosome loss or gain, ploidy changes, and a variety of chromosome aberrations are common in cancer cells. If proliferating cells fail to coordinate centrosome duplication with DNA replication, this will inevitably lead to a change in ploidy, and the formation of monopolar or multipolar spindles will generally provoke abnormal segregation of chromosomes. Indeed, it has long been recognized that errors in the centrosome duplication cycle may be an important cause of aneuploidy and thus contribute to cancer formation. This view has recently received fresh impetus with the description of supernumerary centrosomes in almost all solid human tumors. As the primary microtubule organizing center of most eukaryotic cells, the centrosome assures symmetry and bipolarity of the cell division process, a function that is essential for accurate chromosome segregation. In addition, a growing body of evidence indicates that centrosomes might be imortant for initiating S phase and completing cytokinesis. Centrosomes undergo duplication precisely once before cell division. Recent reports have revealed that this process is linked to the cell division cycle via cyclin-dependent kinase (cdk) 2 activity that couples centriole duplication to the onset of DNA replication at the G1/S phase transition. Alterations in G1/S phase regulating proteins like the retinoblastoma protein, cyclins D and E, cdk4 and 6, cdk inhibitors p16INK4A and p15INK4B, and p53 are among the most frequent aberrations observed in human malignancies. These alterations might not only lead to unrestrained proliferation, but also cause karyotypic instability by uncontrolled centrosome replication. Since several excellent reports on cell cycle regulation and cancer have been published, this review will focus on the role of centrosomes in cell cycle progression, as well as causes and consequences of aberrant centrosome replication in human neoplasias.